Morphology and molecular mobility of plasticized lignins studied with polarization transfer solid-state NMR and SAXS - Åke Henrik-Klemens; Tobias Sparrman; Linnea Björn; Aleksandar Matic; Anette Larsson (Polymer Testing)
Two major challenges in processing and applying lignin materials are their rigidity – being brittle at room temperature and lacking flowability when heated – and their heterogeneity, which causes wide and inconsistent variations in thermal properties. External plasticization is a resource-efficient way to improve the processability and mechanical properties of lignin and lignin-containing materials. However, how plasticizers distribute themselves within the lignin matrix and change its molecular superstructure is not known. In this work, the dispersal of plasticizer and its effect on lignin morphology and molecular mobility were studied using polarization transfer solid-state NMR (ssNMR) and small-angle X-ray scattering (SAXS). Two softwood lignins (Lignoboost and isolated from Norway spruce) were plasticized with three different plasticizers (glycerol, triacetin and diethyl phthalate). The molecular mobility of lignin-plasticizer blends under the glass transition temperature was found to differ substantially, with aprotic plasticizers enabling higher mobility in both types of lignins. The spin diffusion of lignin prior to plasticization was heterogeneous, indicating a heterogeneous chemical environment in the low nanometer range. Upon plasticization, the heterogeneity remained but changed in character. Plasticizer was now distributed unevenly between two lignin phases, but the two phases had achieved more similar dynamics. This convergence suggests the formation of a material with narrower range in physical properties – in line with the observed narrowing of the glass transition upon plasticization. Lignin blended with highly compatible plasticizers were found to have a more swollen morphology as revealed by SAXS. These findings indicate that an appropriate plasticizer will both reduce the temperature and the width of the glass transition, yield a more homogeneous material as well as form a glass that can accommodate stress.